A Critical Analysis of Research Scholar Expectations in Higher Education - Saddaf Ayub, Muhammad Saeed Khan (PJE, 2023)
The study was designed to examine critical analysis of research scholar expectations in higher education at UOH. Objectives of the study were to find out recent scholar’s expectations from university, to explore the social status of enrolling in higher education, to assess the educational preferences and skills and to analyze the economic status of research scholars.101 students of M. Phil program and 15 students of the Ph.D program from different departments (education, agriculture, environmental, mathematics, forestry, management, microbiology) were chosen as the sample of the study.